Effect of dendritic copper powder addition to polyamide 12 in selective laser sintering - Bekem, Aylin; Ozbay, Burcin; Bulduk, Mustafa Enes (GAZI UNIV, FAC ENGINEERING ARCHITECTURE, 2021)
Today, polymer materials have a wide range of usage areas that are from household goods to engineering applications. Therefore, improvements in their properties are essential. The addition of fillers can increase the properties of polymer materials. Filler addition techniques and compositions can vary with the manufacturing methods. It is also possible to use fillers in selective laser sintering (SLS) powder bed fusion additive manufacturing method, which is a new manufacturing method based on the sintering of polymer powders with an infrared laser beam. Although the use of fillers is not very common in this method, the most preferred fillers are ceramic based inorganic materials. However, fine metallic particles could also be used as fillers. This study investigates the processing of dendritic copper powder filled polyamide 12 by SLS method. Powder mixtures in two different filler contents were characterized to determine process parameters, and it was determined that increased energy density should be used. As a result of the physical and mechanical tests of the sintered samples produced using five different parameters, the bending properties and dimensional sensitivity decreased with the filler addition, while surface roughness did not change, and the storage modulus improved.
Keywords: Dendritic copper powder; polyamide 12; selective laser sintering; MECHANICAL-PROPERTIES; Engineering